PENDAMPINGAN KELAS MINI ZOO EDUKATIF UNTUK PENGEMBANGAN GEOPARK PENANGKARAN RUSA MALO KABUPATEN BOJONEGORO - Susilo, Joko; Rahmawati, Laily; Romadhoni, Novita; Wahyuni, Novi; Susanti, Diana (Jurnal Abdi Masyarakat, 2025)
Early childhood education plays an important role in fostering children's growth and character development. However, its implementation often focuses on cognitive aspects and pays little attention to character growth. This community service activity focused on strengthening the function of the Timor Deer Breeding Center in Malo Village, Bojonegoro, through an outdoor learning approach based on an educational mini zoo. The program aimed to improve the quality of early childhood education while optimizing the role of the breeding center as a means of conservation and educational tourism. The implementation methods included needs identification, facility revitalization, mini zoo class assistance, and evaluation. The results of the assistance showed high enthusiasm from the participants and an increase in community visits by 44.26%. These findings confirm that educational mini zoos contribute to character building in children, environmental preservation, and local community empowerment.